The Efficiency of Fluoride Bioactive Glasses in Protecting Enamel Surrounding Orthodontic Bracket. (25th March 2021) - Abbassy, Mona Aly; Bakry, Ahmed Samir; Hill, Robert
Abstract : Objectives . The aim of this study was to evaluate the protective effect of using four different fluoride bioactive enamel sealers against an acidic erosion challenge. Materials and Methods . A sample of 50 freshly extracted sound upper premolars had their buccal surface bonded to 50 orthodontic brackets using Transbond PLUS color change adhesive; the first four groups had four compositions of fluoride bioactive glasses based on 37 mol% SiO2, 43.9-53.9 mol% CaO, 6.1 mol% P2 O5 and CaF2, and 0-10 mol% of Na2 O applied to their surfaces and the fifth group served as control (which was not treated by any bioactive sealer). All specimens were challenged by 1% citric acid for 18 minutes which was stirred by a magnetic stirrer. The enamel surfaces next to the orthodontic brackets were examined by SEM. The Wilcoxon signed-rank test was used to compare the area covered by the fluoride bioactive pastes before/after erosion (p < 0.05 ). Samples from the layer formed on top of the examined teeth were tested before/after erosion to be examined by the attenuated total reflectance Fourier-transform infrared spectroscopy (FTIR/ATR). Results . The FTIR/ATR test showed that fluoride bioactive pastes' applications resulted in the formation of a hydroxyapatite-rich layer; the SEM analysis showed that the aforementioned layer significantly resisted erosion challenge when compared to the control group (p < 0.05 ). Conclusions . Fluoride bioactive pastes can efficiently protect the enamel surfaces next to orthodontic brackets from acidic erosion challenges.